2020
DOI: 10.1021/acs.analchem.0c00506
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Reversible Fluorescent Probe for Real-Time Live-Cell Imaging and Quantification of Mitochondrial ATP

Abstract: Real-time imaging and quantification of adenosine triphosphate (ATP) fluctuation in cells are significant for understanding the relationship between energy metabolism and cell functions. However, few synthetic fluorescent probes have been reported to tackle this challenge due to lack of accurate fluorescence readout and suitable response concentration. Herein we designed and synthesized a ratiometric fluorescent probe (Rh6G–ACFPN) for quantitatively detecting the fluctuation of mitochondrial ATP in living cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 60 publications
3
61
0
Order By: Relevance
“…In vitro and in vivo studies in the clinical pathology environment had proved remarkable stability of NIRII‐RT4 (Figure 1 H, Figure 4 and Figure S21), thus the emission change in liver of living mice reflected the actual ATP fluctuation. From the cells imaging experiments with an NIR ATP probe ACF‐ATP4, [38] we further demonstrated the increase of intracellular ATP in hepatocytes during hepatotoxicity (Figure S26,S27). Moreover, real‐time experiments showed that NIRII‐RT‐ATP also can image hepatotoxicity even within 1 h APAP (300 mg kg −1 ) treated (Figure 6 B and D).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…In vitro and in vivo studies in the clinical pathology environment had proved remarkable stability of NIRII‐RT4 (Figure 1 H, Figure 4 and Figure S21), thus the emission change in liver of living mice reflected the actual ATP fluctuation. From the cells imaging experiments with an NIR ATP probe ACF‐ATP4, [38] we further demonstrated the increase of intracellular ATP in hepatocytes during hepatotoxicity (Figure S26,S27). Moreover, real‐time experiments showed that NIRII‐RT‐ATP also can image hepatotoxicity even within 1 h APAP (300 mg kg −1 ) treated (Figure 6 B and D).…”
Section: Resultsmentioning
confidence: 75%
“…The fluorescence OFF‐ON switching of NIRII‐RT4 amide derivative NIRII‐RT‐pH is very similar to that of the classic CS dyes (NIR rhodamine derivatives) and their amide derivatives, [26] indicating that, like the classic CSs, the novel NIR‐II dye NIRII‐RT4 (or NIRII‐RT3) could be used as platforms to design NIR‐II fluorescent probes. To further verify this, we then constructed NIRII‐RT‐ATP and NIRII‐RT‐Hg (Figure 5 D) as novel NIR‐II fluorescent probes for detecting adenosine triphosphate (ATP) [38] and Hg 2+ , [39] respectively. As shown in Figure 5 E, like probe NIRII‐RT‐pH, NIRII‐RT‐ATP itself had no fluorescence.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…[43] In vitro and in vivo studies in the clinical pathology environment had proved remarkable stability of NIRII-RT4 (Figure 1H,F igure 4a nd Figure S21), thus the emission change in liver of living mice reflected the actual ATP fluctuation. From the cells imaging experiments with an NIR ATPp robe ACF-ATP4, [38] we further demonstrated the increase of intracellular ATPi nh epatocytes during hepatotoxicity (Figure S26,S27). Moreover,r eal-time experiments showed that NIRII-RT-ATPa lso can image hepatotoxicity even within 1hAPAP (300 mg kg À1 )t reated (Figure 6B and D).…”
Section: Angewandte Chemiementioning
confidence: 71%
“…Fluorescence (Aptamer) 0.125−2 mM 19 μM [1] Fluorescence (Split Aptamer) 0.03−2 mM 30 μM [2] Fluorescence (Small organic molecules) None (Resonpse range 2−9 mM) None [3] Fluorescence (Aptamer) 0−1.6 mM 78 μM [4] Fluorescence (Aptamer) None (Resonpse range 2−8 mM) None [5] Fluorescence (Aptamer) 0.1−2 mM 18 μM This work S-8…”
Section: Methods Linear Range Lod Referencementioning
confidence: 99%